Identification and Characterization of the Diverse Stress-Responsive R2R3-RMYB Transcription Factor from Hibiscus sabdariffa L. - Bahaeldeen Babikar Mohamed; Beenish Aftab; Muhammad Bilal Sarwar; Bushra Rashid; Zarnab Ahmad; Sameera Hassan; Tayyab Husnain (International Journal of Genomics)
Various regulatory proteins play a fundamental role to manage the healthy plant growth under stress conditions. Differential display reverse transcriptase PCR and random amplification of cDNA ends (RACE) was used to explore the osmotic stress-responsive transcripts. We identified and characterized the salt stress-responsive R2R3 type RMYB transcription factor from Hibiscus sabdariffa which has an open reading frame of 690 bp, encoding 229 long chain amino acids. In silico analysis confirmed the conserved R2 and R3 domain as well as an NLS-1 localization site. The deduced amino acids of RMYB shared 83, 81, 80, 79, 72, 71, and 66% homology with Arabidopsis thaliana, Glycine max, Oryza sativa, Zea maize, Malus domestica, Populus tremula × Populus alba, and Medicago sativa specific MYB family, respectively. We observed the gene upregulation in stem, leaf, and root tissue in response to abiotic stress. Furthermore, RMYB gene was cloned into plant expression vector under CaMV35S promoter and transformed to Gossypium hirsutum: a local cotton cultivar. Overexpression of RMYB was observed in transgenic plants under abiotic stresses which further suggests its regulatory role in response to stressful conditions. The RMYB transcription factor-overexpressing in transgenic cotton plants may be used as potential agent for the development of stress tolerant crop cultivars.